PENGARUH CAPITAL ADEQUACY RATIO (CAR), NON PERFORMING FINANCING (NPF), FINANCING TO DEPOSIT RATIO (FDR), DAN OPERATIONAL EFFICIENCY RATIO (OER) TERHADAP RETURN ON ASSET (ROA) PADA BRI SYARIAH TAHUN 2009-2014 - Ramadhani, Fitri; Maulida, Yusni; Indrawati, Toti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This research aims to analyze the effect brought about by the variable of Capital Adequacy Ratio (CAR), Non Performing Financing (NPF), Financing To Deposit Ratio (FDR), and Operational Efficiency Ratio (OER) To Return On Asset (ROA) at BRI Syariah. This research use descriptive analysis method and the method or tool. Analysis of partially and simultaneous (multiple liniar regresi analysis by using its facilities program eviews version 9.5 SV). From the results of testing that has been done, the simultaneous regresion test (test F) show that the Capital Adequacy Ratio (CAR), Non Performing Financing (NPF), Financing to Deposit Ratio (FDR), and Operational Efficiency Ratio (OER) along the same influential and significantly to the Return On Asset (ROA). partial regression test (test t) indicates that the variable Capital Adequacy Ratio (Car) has significant influence again Return On Asset (ROA, Non Performing Financing (NPF) variable do not effect significantly to Return On Asset (ROA), Variable Financing to Deposit Ratio (FDR) effect significantly to the Return On Asset (ROA), and Operational Efficiency Ratio (OER) influential variables significantly to Return On Asset (ROA).Keywords: Return On Asset (ROA), Capital Adequacy Ratio (CAR), Non Performing Financing (NPF), Financing to Deposit Ratio (FDR), and Operational Efficiency Ratio (OER)